Strengthening Employee Performance Through Work Culture and Motivation - Hidayat, Wahyu; Dantika, Fina Azizah (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Employee performance refers to the degree of a person's performance in carrying out his duties responsibly in accordance with established regulations. The main factor in achieving superior employee performance cannot be separated from corporate culture and work motivation. Organizational culture is the identity of an organization therefore, it is important for every organization to have and maintain a culture to distinguish one organization from another. Motivation is a factor that drives individual activities in an organization to achieve the expected goals. The purpose of this study is to determine the impact of employee performance on the organization. This research uses Qualitative research methods. The results of this study lead to the importance of company culture and motivation that have an impact on employee performance.